Globalization processes and their impact on library activity - S. S. Araslanova (Библиосфера)
The current stage of society development is conditioned by the intense globalization processes, during which the local culture integration with the world international environment takes place. Globalization processes have affected all political, social and cultural institutions, including libraries. Physical, language, national boundaries cease to exist for libraries. Social-cultural innovations in any field become in the public domain as soon as possible with the Internet advances. A single global information space is formed. Thanks to the World Wide Web unimaginable before amounts of knowledge and information are available to human. However, according to many scientists views globalization has not only positive sides. Globalization processes can lead to a loss of local knowledge systems of national cultures, which could also benefit the global community. In this regard, the most important function of libraries is to search, preserve, systematize, and provide access to information resources of their region. Thus, the library must ensure the cultural content generation, help to overcome globalization negative effects. Library becomes an active subject of regional cultural policy, an organizer and coordinator of national and regional book culture heritage conservation.